Epidemiology of severe burns in North-East of Iran: How is the burn size different in a developing country from developed ones? - Majid Khadem-Rezaiyan; Hosein Aghajani; Ali Ahmadabadi; Minoo Zanganeh; Seyed Hassan Tavousi; Alireza Sedaghat; Saeid Eslami Hasanabadi (Elsevier, 2020)
In contrast to the high prevalence of burn injuries in the low and middle-income countries, accurate data about the epidemiological and etiologic pattern of burns in these countries is limited and scattered. The aim of this study is to present accurate information about the demographical and geographical pattern of burns severely enough to be hospitalized, in the northeast of Iran, in the years 2010-2015. In this cross-sectional study, we included all patients admitted because of acute burn injuries to Imam Reza Burn Center. There were 3352 admissions and approximately three-quarter of them were from Razavi Khorasan province (73.3%, 2458). The mean age of patients was 26.5 ± 19.3 years and 2065 (62%) were male. The overall mortality rate was 21.4% (7 1 7). The mean of burnt total body surface area (TBSA) (50.7 ± 26.3%), mortality rate (41.3%) hospitalization period (20.1 ± 16.7 days) and Abbreviated Burn Severity Index (8.8 ± 3.1) were higher in patients referred from the South Khorasan Province (all p < 0.001). Patients referred from other provinces had the second rank for all mentioned indices. In 63% of patients, burnt TBSA was ≥20% and the mortality rate in this group was 10 folds more than patients with burns less than 20% of TBSA. Burn injury was more common in individuals with lower skills and competencies. About two-thirds of patients had a burnt TBSA ≥ 20% and it was the most important factor involved in high mortality rate in this center. In designing preventive policies in developing countries, safety aspects of mechanisms and activities which lead to severe forms of burn injury must be considered as a priority. Keywords: Burns, Epidemiology, Catchment area, Mortality, Hospital stay